Educação e PROUNI: política de inclusão social na perspectiva transdisciplinar - Santos, Nadja Maria Codá dos (2011)
This study is articulated with national project of research called Programme University For All - PROUNI and Social Inclusion", developed, in the period 2007 to 2010, by the core of Study Research on Education and Methodological Issues (NEMESS) of The Pos-graduate Studies of Social Service of PUC-SP. It has been financed by the Centre of Education in partnership with the Coordination of Personal Improvement of Superior Level (CAPES) and with the National Institute of Studies and Educational Research Anísio Teixeira (INEP). The aim is to analyse by method transdisciplinar of research how PROUNI can promote social inclusion of students from low rent. This study contextualize the brazilians educational policies and the means of concept of social inclusion by access to higher education, advocated by the PROUNI. There is the revision of the theories and visions of the studies of the transdisciplinary in order to sustain method of research that is capable of catch and understand the perceptions, impressions, expectations and anxieties of the scholarships about the personal and professional changes offered by the PROUNI. In the research, there are references to documents and laws of the federal government, and to the authors of the areas of education, social policies, inclusion/exclusion and transdisciplinary. It has been carried focal group of discussions with the scholarships of PROUNI, in the city of São Paulo. The analysis of the focal groups s content has been through by the organisation of analytical categories: a) Accessibility and Inclusion/ Social Exclusion; b) Social Advancement (personal and professional); c) Prejudice and stigma; d) Social assistance and support to the Learning; e) Disability of Public Education and Reform of the Education system. The scholarships valid the educational policy of the federal government, however, understand that the aim of social inclusion is not carried out in full once again because many young people and adults are still without conditions means to enter in the university. The relationship between inclusion and social exclusion is still to be reproduced in the social coexistence of students and teachers, in the educational institutions that have joined the PROUNI